Residual Gait Deviations in Children Treated by Medial Open Reduction for Developmental Dysplasia of the Hip at Long-Term Follow-up: A Comparison With Healthy Controls - Demirel, Mehmet; EVRENDİLEK, HALENUR; AKALAN, NAZİF EKİN; Bilgili, Fuat; Meric, Emre; Kuchimov, Shavkat; ÖNERGE, KÜBRA (Springer, 2024)
Purpose This study aimed to analyze and compare gait patterns and deviations at long-term follow-up in children who received medial open reduction (MOR) before 18 months for unilateral or bilateral hip developmental dysplasia (DDH). Methods A retrospective chart review was conducted on children who underwent MOR. The study population was divided into two groups: the unilateral group, including unilateral (five children with unilateral) and bilateral (five children with bilateral DDH). Ten healthy children were recruited for the control group. Spatiotemporal, kinematic, stiff-knee gait (SKG), and kinetic gait characteristics were analyzed. Results Stance time was significantly shorter in both the unilateral (median [IQR]; 590 ms, [560.0-612.5] and bilateral (575 ms, [550-637.5]) groups than in the control group (650, [602.5-677.5]) (p < 0.001), whereas swing time did not differ substantially (p = 0.065) There was no considerable difference in the mean knee flexion at swing between the unilateral (31.6 degrees, [30-36]) and control (30.11 degrees, [27.8-33.6] groups (p > 0.05), but the bilateral group (28.5 degrees, [24.9-32.1]) showed the lower values than the other groups (p < 0.001 for bilateral vs unilateral group; p = 0.008 bilateral vs unilateral group). All the SKG parameters significantly differed among the groups in multi-group comparisons (p < 0.001 for each parameter). Three children had borderline SKG, and two had not-stiff limbs in the unilateral group. In the bilateral group, four children had stiff limbs, and one had borderline SKG. Most kinetic gait parameters were not statistically different between groups (p > 0.05). Conclusion This study has revealed notable deviations in gait patterns of children with DDH treated by MOR at long-term follow-up compared to healthy children's gait. MOR could negatively affect pelvic motion during gait due to impaired functions of the iliopsoas and adductor muscles, and SKG can be encountered secondary to iliopsoas weakness.
Keywords: Developmental Dysplasia of the Hip; Gait Analysis; Medial Open Reduction; Residual Gait Deviations; Stiff-Knee Gait